Analytical Quality by Design approach in development and optimization of HPLC method for assay of angiotensin – converting enzyme inhibitor in tablets - Veronika Popovska Jakimovska; Ana Atanasova; Filip Gogu; Maja Stevanoska; Emilija Arsovska Popovska; Packa Antovska; Suzana Trajkovic Jolevska; Jasmina Tonic Ribarska (Makedonsko Farmacevtski Bilten)
Implementation of analytical quality by design approach is a helpful tool in development of a robust analytical method which is applicable throughout the lifecycle of the product. This model is perfect strategy for analytical method development, in order to reduce outof-trend (OOT) and out-of-specification (OOS) results and to achieve high degree of robustness, providing cost-effective analytical method. The aim of this study was to implement a software which uses experimental design plans as an efficient and fast tool for development of method for quantitative determination of content of ACE inhibitor in tablets. Using statistical models in method development and optimization, the effect of each factor on responses of interest were calculated and the data were used to find the optimal chromatographic conditions. Best chromatographic separation within run time of 13 minutes was achieved on column Zorbax SB C18, 150 x 4.6 mm, (5 µm), using a mixture of 15 mM phosphate buffer pH 1.8 and acetonitrile as a mobile phase, with gradient elution and column temperature maintained at 60 °С. The validated method is specific, linear, accurate, precise and robust for the determination of angiotensin - converting enzyme inhibitor in tablets.